Are we really mapping psychosis risk? Neuroanatomical signature of affective disorders in subjects at ultra high risk - Modinos, G; Allen, P; Frascarelli, M; Tognin, S; Valmaggia, L; Xenaki, L; Keedwell, P; Broome, M; Valli, I; Woolley, J; Stone, J; Mechelli, A; et al. (Cambridge University Press, 2014)
Background. The majority of people at ultra high risk (UHR) of psychosis also present with co-morbid affective disorders such as depression or anxiety. The neuroanatomical and clinical impact of UHR co-morbidity is unknown.